CO2 Hydrogenation on Cu/Al2O3: Role of the Metal/Support Interface in Driving Activity and Selectivity of a Bifunctional Catalyst. Issue 39 (19th August 2019) - Lam, Erwin; Corral‐Pérez, Juan José; Larmier, Kim; Noh, Gina; Wolf, Patrick; Comas‐Vives, Aleix; Urakawa, Atsushi; Copéret, Christophe
Abstract: Selective hydrogenation of CO2 into methanol is a key sustainable technology, where Cu/Al2 O3 prepared by surface organometallic chemistry displays high activity towards CO2 hydrogenation compared to Cu/SiO2, yielding CH3 OH, dimethyl ether (DME), and CO. CH3 OH formation rate increases due to the metal–oxide interface and involves formate intermediates according to advanced spectroscopy and DFT calculations. Al2 O3 promotes the subsequent conversion of CH3 OH to DME, showing bifunctional catalysis, but also increases the rate of CO formation. The latter takes place 1) directly by activation of CO2 at the metal–oxide interface, and 2) indirectly by the conversion of formate surface species and CH3 OH to methyl formate, which is further decomposed into CH3 OH and CO. This study shows how Al2 O3, a Lewis acidic and non‐reducible support, can promote CO2 hydrogenation by enabling multiple competitive reaction pathways on the oxide and metal–oxide interface. Abstract : More than one way : CO2 hydrogenation on Cu/Al2 O3 is studied by combining state‐of‐the art synthetic methods with operando spectroscopy and computational chemistry to elucidate possible reaction mechanisms forming CH3 OH, CO, and CH3 OCH3 .